IMPLEMENTASI METODE PROBLEM BASED LEARNING DALAM MENINGKATKAN PEMAHAMAN FIKIH WANITA SANTRI DI PONDOK PESANTREN AL-AMIEN AMBULU - Novia Nurul Imamah; M Imam Bukhori (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
The learning of women's fiqh in Islamic boarding schools requires an appropriate approach to improve students' understanding of Islamic legal issues encountered in daily life. One of the approaches employed is Problem-Based Learning (PBL), a learning model that emphasizes problem-solving to encourage students' active participation. This study aims to describe the planning and implementation of PBL, analyze the improvement of students' understanding, and identify the supporting and inhibiting factors in its implementation at Al-Amien Islamic Boarding School, Ambulu. This research employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing. The findings reveal that the implementation of PBL begins with systematic planning, followed by the presentation of contextual problems, individual analysis, argumentation, and collaborative discussion. The learning materials were based on the book Uyun al-Masail Linnisa’: Sumber Rujukan Permasalahan Wanita. The implementation of PBL enhanced students' understanding of women's fiqh, analytical skills, critical thinking, and their ability to apply Islamic law in daily life. Supporting factors included teacher competence, the availability of learning resources, and students' learning motivation, while inhibiting factors included differences in students' academic abilities, limited instructional time, and a lack of self-confidence.